1997
DOI: 10.2337/diacare.20.12.1814
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Responses in Patients With IDDM

Abstract: There is no evidence of impairment of the exercise response in subjects with long-standing diabetes, and the apparent fall in left ventricular EF at peak exercise could be related to hemodynamic adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 32 publications
(59 reference statements)
2
18
0
Order By: Relevance
“…These abnormalities could thus be related to increased dead space ventilation, as previously described in diabetic patients. 31 In summary, our study showed that the severity of microalbuminuria in type 2 diabetic patients was correlated with impaired cardiovascular function and oxygen transport during exercise. A unified hypothesis may herein be generated that microalbuminuria may signal a state of generalized microvascular dysfunction, with increased capillary permeability to macromolecules, such as plasma proteins.…”
Section: Discussionmentioning
confidence: 90%
“…These abnormalities could thus be related to increased dead space ventilation, as previously described in diabetic patients. 31 In summary, our study showed that the severity of microalbuminuria in type 2 diabetic patients was correlated with impaired cardiovascular function and oxygen transport during exercise. A unified hypothesis may herein be generated that microalbuminuria may signal a state of generalized microvascular dysfunction, with increased capillary permeability to macromolecules, such as plasma proteins.…”
Section: Discussionmentioning
confidence: 90%
“…However, although heart rate and systolic blood pressure increased as expected during exercise, diastolic blood pressure decreased by ϳ10 mmHg. Diastolic dysfunction during exercise, not accompanied by systolic dysfunction or altered cardiac output response, has been reported by several authors (32)(33)(34) in type 1 diabetic patients with no evidence of autonomic neuropathy, leading to the hypothesis that alterations in diastolic filling may represent the earliest functional defect of diabetic cardiomyopathy. Surprisingly, however, an exercise-induced reduction in diastolic blood pressure in type 1 diabetes has not been previously reported.…”
Section: Discussionmentioning
confidence: 91%
“…We believe that the experimental design used in previous exercise studies obscured recognition of this finding. The large majority of previous exercise studies in type 1 diabetes used incremental maximal tests (33,35,36) or brief periods of submaximal exercise (37); furthermore, diastolic blood pressure was seldom reported, and glycemic levels during exercise were never controlled (introducing the confounding effect of concomitant hypoglycemia, which may independently lower blood pressure and stimulate the ANS).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, VO 2max was similar between the groups. This is in keeping with previous studies in which patients with uncomplicated type 1 diabetes had a normal aerobic exercise capacity (40). We chose the intensity of isometric exercise based on individual muscular strengths, rather than on VO 2max , because use of the latter would lead to different work loads if groups differed with respect to VO 2max .…”
mentioning
confidence: 85%